(untitled) (Research, Society and Development, 2020)
Water is an essential component for the maintenance of life, essential to human needs and professional activities. In food services, water is used in several activities, mainly on hygiene during the production steps. However, if its quality is compromised, due to the presence of pathogenic microorganisms, for example, it can become a vector for the transmission of waterborne diseases. The objective of this work was to evaluate the presence of total coliforms (TC) and Escherichia coli in drinking water used in production in thirty food service units in the city of Recife/PE. The identification methodology for TC and E. coli was the presence/absence test, using chromogenic substrate X-GAL and fluorogenic MUG. TC was present in thirty-two samples, of which six units were also positive for E. coli. It is concluded that of the total of thirty establishments investigated, about 54% used water in the production of food that did not reached the microbiological standard recommended by Brazilian legislation, requiring corrective and educational measures to ensure that there are no health problems.